2012
DOI: 10.3342/ceo.2012.5.s1.s82
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Vibrant Soundbridge Middle Ear Implant in Cantonese-Speaking Mixed Hearing Loss Adults

Abstract: ObjectivesTo investigate the aided benefits, speech recognition in quiet and in noise, change in hearing and subjective report of satisfaction on mixed hearing loss adults implanted with Vibrant Soundbridge (VSB) middle ear implant.MethodsEight Cantonese speaking adult patients with mixed hearing loss were enrolled in a single-subject, repeated measures prospective study design. Audiometric testing, including air and bone conduction and word recognition under sound-field were conducted before surgery. Device a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…The functional gain of the VSB at 3 months ranged from 12.5 dB to 43.4 dB HL, averaging at 29.6 dB. Studies evaluating gain over time showed no change between 3 and 6 months and between 3 and 40 months …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The functional gain of the VSB at 3 months ranged from 12.5 dB to 43.4 dB HL, averaging at 29.6 dB. Studies evaluating gain over time showed no change between 3 and 6 months and between 3 and 40 months …”
Section: Resultsmentioning
confidence: 98%
“…Nineteen articles were identified that investigated the effectiveness of the VSB. These included 16 single cohort before‐after studies, two concurrent cohort studies, and one nonrandomized clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, because QOL-HISQUI 29 Significant changes in self-reported QOL questionnaires were found in our study. Overall, patient satisfaction with the VSB was very good, suggesting that patients perceived system benefit in their daily life (24,26,27,30,31). Interestingly, our patients rated a mean HISQUI 29 score corresponding to ''very good'' sound quality.…”
Section: Complicationsmentioning
confidence: 67%
“…29 Nevertheless, all studies on VSB in mixed or conductive hearing loss consistently report great improvements in terms of "functional gain" and speech recognition compared with the unaided situation, and hence the VSB can be considered a very effective treatment. 1,5,8,[28][29][30][31]33,36 Unfortunately, attempts to compare the hearing results of the VSB at conductive or mixed hearing loss with "best fitting" CHA in a convincing manner are rare. 1 A requirement for such studies is a prospective design with a detailed report of long-range systematic attempts for optimal fitting of CHA (with testing of multiple different types and brands).…”
Section: Surgical and Hearing Outcomesmentioning
confidence: 99%